Sugary drink consumption and tooth decay relationship in diabetes mellitus patients - Prasetyo, Eric Priyo; Widjiastuti, Ira; Sampoerno, Galih; Juniarti, Devi Eka; Wijanarko, Christina Immee; Kharisna, Deaniddo; Syahria, Hania Dana; Nabila, Rizka Affan; Suardita, Ketut (Conservative Dentistry Journal, 2024)
Introduction: Diabetes mellitus is a chronic metabolic disorder characterized by high blood sugar levels. It is a global health problem that can increase the risk of tooth decay and requires conservative dental treatment. Several factors impact the severity of tooth decay, sugary drink consumption is one of them. This study aimed to investigate the association between tooth decay in patients with diabetes mellitus who regularly consume sugary drink versus those who do not. These patients visited Conservative Dentistry Section, Universitas Airlangga Dental Hospital Surabaya, Indonesia, during Jan-Mar 2023. Methods: This study involved 37 patients with diabetes mellitus and posterior tooth decay. Demographic data were gathered from personal interview and dental records. Statistical analysis was done using chi-square analysis. Results: sugary drink consumption has a significant difference (p<0.05) among the patients with posterior tooth decay and diabetes mellitus. Conclusion: sugary drink consumption influences the severity of tooth decay in diabetes mellitus patients.